Pole piece, preparation method thereof and battery
By designing a composite layer structure in the electrode sheet, including the recess and the liquid absorbing layer, the penetration path of the electrolyte is optimized, and the problem of degradation of the electrolyte penetration ability caused by the increase in the thickness of the electrode sheet in lithium-ion batteries is solved, and the rate performance is improved.
Patent Information
- Application Number
- CN202411411792.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-07
AI Technical Summary
The increase in the thickness of the electrode sheet in lithium-ion batteries leads to a decrease in the penetration capacity of the electrolyte, and the difficulty in migration of lithium ions, limiting the rate performance.
A pole sheet structure is designed, including a current collector and a composite layer. The composite layer is composed of a first active material layer and a liquid absorbing layer. A recess is formed on the first active material layer, and the liquid absorbing layer covers the first surface and the inner surface of the recessing portion. Optimize the penetration path of the electrolyte.
Through the optimized structure of the liquid absorbing layer, the transmission path of lithium ions is shortened, the wetting effect of the electrolyte is improved, the concentration polarization inside the electrode sheet is reduced, and the rate performance is improved.
Smart Images

Figure CN119275232A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery manufacturing technology, and in particular to a pole piece, a method for preparing a pole piece, and a battery. Background Art
[0002] With the rapid development of the new energy vehicle industry, the requirements for the energy density of lithium-ion batteries are getting higher and higher. The ideal way to improve the energy density of lithium-ion batteries is to increase the thickness of the pole piece to increase the content of active substances. However, in lithium-ion batteries, the thicker the pole piece, the worse the penetration of the electrolyte, which increases the concentration polarization inside the pole piece during the charge and discharge process of the lithium-ion battery, making lithium ion migration difficult, which will limit the rate performance of the lithium-ion battery to a certain extent. Summary of the invention
[0003] The embodiments of the present application provide a pole piece, a method for preparing the pole piece, and a battery, which can solve the technical problem of large concentration polarization inside the pole piece.
[0004] In a first aspect, an embodiment of the present application provides a pole piece, comprising: a current collector and a composite layer arranged on the current collector, the composite layer comprising a first active material layer and a liquid absorption layer arranged in sequence in a direction away from the current collector, the first active material layer having a first surface away from the current collector, and a recess extending from a part of the first surface to the interior of the first active material layer is also formed on the first active material layer, and the liquid absorption layer covers the first surface and the inner surface of the recess.
[0005] In one embodiment, the recess includes at least one of a groove and a through hole.
[0006] In one embodiment, the recess is a long strip-shaped groove extending along a first direction of the first active material layer, and a length of the groove extending in the first direction is less than or equal to a length of the first active material layer in the first direction.
[0007] In one embodiment, along a direction approaching the current collector, the width of the recess remains unchanged or becomes smaller.
[0008] In one embodiment, the side wall of the recess is a straight wall or a curved wall.
[0009] In one embodiment, when cut along the thickness direction of the first active material layer, the cross section of the concave portion is in a V-shape, trapezoid, square, semicircular or elliptical shape.
[0010] In one embodiment, there are a plurality of the recesses, the plurality of recesses are spaced apart, and a distance between two adjacent recesses is 0.01 mm to 100 mm.
[0011] In one embodiment, the depth of the recess is smaller than the thickness of the first active material layer.
[0012] In one embodiment, the average width of the concave portion is 1 μm to 300 μm.
[0013] In one embodiment, the thickness of the liquid absorbing layer is 0.2 μm to 50 μm.
[0014] In one embodiment, the thickness of the liquid absorbing layer is 0.2 μm to 10 μm.
[0015] In one embodiment, the porosity of the liquid absorbing layer is 5% to 99%.
[0016] In one embodiment, the thickness of the first active material layer is greater than 30 μm.
[0017] In one embodiment, the thickness of the pole piece is greater than 60 μm.
[0018] In one embodiment, the liquid absorbing layer is a mixed layer including at least a first binder and a first conductive agent.
[0019] In one embodiment, the first active material layer is a mixed layer including a first active material, a second binder, and a second conductive agent.
[0020] In one embodiment, the mass content of the second conductive agent in the first active material layer is less than the mass content of the first conductive agent in the liquid absorption layer; and / or the oil absorption value of the first conductive agent is greater than the oil absorption value of the first active material.
[0021] In one embodiment, the content of the first active material in the first active material layer is greater than 50 wt %, and the content of the first conductive agent in the liquid absorbing layer is greater than 50 wt %.
[0022] In one embodiment, in the first active material layer, the content of the second conductive agent increases along a direction approaching the current collector.
[0023] In one embodiment, in the first active material layer, the first active material is first active material particles, and the average particle size of the first active material particles increases along the direction close to the current collector. In one embodiment, the first conductive agent includes at least one of a conductive carbon material and a conductive ceramic.
[0024] In one embodiment, the conductive carbon material includes at least one of carbon black, carbon nanotubes, carbon fibers, acetylene black, graphite and graphene.
[0025] In one embodiment, the specific surface area of the first conductive agent is 1 m 2 / g~1000m 2 / g; and / or, the D50 particle size of the first conductive agent is 1nm~50μm; and / or, the oil absorption value of the first conductive agent is greater than or equal to 500mL / 100g; and / or, the conductivity of the first conductive agent is 3000S·cm~12000S·cm.
[0026] In one embodiment, the first binder includes at least one of carboxymethyl cellulose, polyacrylic acid, polyvinylidene fluoride, polytetrafluoroethylene and styrene-butadiene rubber.
[0027] In one embodiment, the liquid absorbing layer includes 1 wt% to 80 wt% of the first conductive agent, 10 wt% to 99 wt% of the first binder, and the liquid absorbing layer further includes 0 wt% to 30 wt% of a dispersant.
[0028] In one embodiment, the dispersant includes at least one of anhydride, polyvinyl pyrrolidone, sulfate ester salt, poly(N-vinyl acetamide), polyvinyl alcohol, sulfonate and polyethylene glycol.
[0029] In one embodiment, the liquid absorbing layer includes 58 wt % to 75 wt % of the first conductive agent, 12.5 wt % to 30 wt % of the first binder, and 8 wt % to 12.5 wt % of the dispersant.
[0030] In one embodiment, the dispersant includes at least one of an ionic dispersant, a non-ionic dispersant and a polymer dispersant.
[0031] In one embodiment, the porosity of the liquid absorbing layer is at least greater than the porosity of the first active material layer.
[0032] In one embodiment, the concave portion is a laser-etched portion.
[0033] In one embodiment, the composite layer further includes a second active material layer, and the second active material layer is disposed on the surface of the liquid absorbing layer and away from the first active material layer.
[0034] In one embodiment, the number of the composite layers on a single side of the current collector is multiple, and the multiple composite layers are stacked.
[0035] In a second aspect, an embodiment of the present application further provides a method for preparing a pole piece, comprising:
[0036] Preparing a first active material layer on a current collector, wherein the first active material layer has a first surface away from the current collector, and a concave portion extending from the first surface to an interior of the first active material layer is formed on the first active material layer;
[0037] The first slurry is subjected to a film-forming treatment on the first surface and the recessed portions of the first active material layer to obtain a liquid absorbing layer.
[0038] In one embodiment, preparing the first active material layer on the current collector includes:
[0039] Performing a film-forming process on the current collector using the second slurry to obtain a first active material layer;
[0040] Laser etching is performed on a portion of the first active material layer from a side of the first active material layer away from the current collector to generate a concave portion.
[0041] In one embodiment, the step of performing a film-forming process on the first surface and the concave portion of the first active material layer to obtain a liquid absorbing layer comprises:
[0042] Providing a first slurry, wherein the first slurry includes a first solvent, a first conductive agent, and a first binder;
[0043] Applying the first slurry on the first surface and the inner surface of the concave portion to obtain a first wet film layer;
[0044] The first wet film layer is dried to evaporate the first solvent, thereby obtaining a liquid absorbing layer.
[0045] In one embodiment, the content of the first solvent in the first slurry is 10wt% to 97wt%; and / or, the solid content in the first slurry is 3wt% to 90wt%; and / or, the viscosity of the first slurry is 10cp to 15000cp; and / or, the first solvent includes at least one of water, N-methylpyrrolidone, ethylene glycol and isopropanol.
[0046] In one embodiment, the preparation process of the first active material layer includes:
[0047] Coating a second slurry on the current collector to obtain a second wet film layer, wherein the second slurry includes a first active material, a second binder, a second conductive agent, and a second solvent;
[0048] The second wet film layer is dried to evaporate the second solvent, thereby obtaining a first active material layer.
[0049] In one embodiment, the method for preparing the pole piece further includes:
[0050] Coating a third slurry on a side of the liquid absorbing layer away from the current collector to obtain a third wet film layer, wherein the third slurry includes a second active material, a third solvent, a third conductive agent and a third binder;
[0051] The third wet film layer is dried to evaporate the third solvent, thereby obtaining a second active material layer.
[0052] In a third aspect, an embodiment of the present application further provides a battery, comprising a pole piece as described in the first aspect of the embodiment of the present application or a pole piece prepared by the method for preparing the pole piece as described in the second aspect of the embodiment of the present application.
[0053] Beneficial effects of the embodiments of the present application:
[0054] In an embodiment of the present application, a pole piece includes a current collector and a first active material layer, a recess is formed on the first active material layer, the opening of the recess faces outward but the recess extends toward the interior of the first active material layer, and the pole piece also includes a liquid absorption layer, which is combined with the first active material layer and covers the first surface of the first active material layer and the inner surface of the recess. Compared with the first active material layer, the liquid absorption layer has a better ability to absorb electrolyte, so that the electrolyte can preferentially penetrate into the interior of the first active material layer through the portion of the liquid absorption layer located in the recess, shortening the transmission path of lithium ions, improving the wetting effect of the electrolyte on the pole piece, and increasing the probability of contact between the active material particles inside the pole piece and the electrolyte; and the liquid absorption layer can also be used as an electrolyte carrier to store electrolyte, so that during the charging and discharging process of the pole piece, the electrolyte stored in the liquid absorption layer can be quickly supplied to the first active material layer. Therefore, when the liquid absorption layer is located on the inner surface of the recess, the liquid absorption layer cooperates with the recess to form a "fast channel", so that the electrolyte can quickly enter the first active material layer, promote the transmission of lithium ions in the electrode and increase the migration speed of lithium ions, thereby reducing the concentration polarization inside the electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0056] Figure 1 The cross-sectional structure of the pole piece provided in the embodiment of the present application is shown in FIG. Figure 1 ;
[0057] Figure 2 The cross-sectional structure of the pole piece provided in the embodiment of the present application is shown in FIG. Figure 2 ;
[0058] Figure 3 The cross-sectional structure of the pole piece provided in the embodiment of the present application is shown in FIG. Figure 3 ;
[0059] Figure 4 The cross-sectional structure of the pole piece provided in the embodiment of the present application is shown in FIG. Figure 4 ;
[0060] Figure 5 The cross-sectional structure of the pole piece provided in the embodiment of the present application is shown in FIG. Figure 5 ;
[0061] Figure 6 The cross-sectional structure of the pole piece provided in the embodiment of the present application is shown in FIG. Figure 6 ;
[0062] Figure 7 is a schematic diagram of a top view of the structure of the first active material layer in the pole piece provided in an embodiment of the present application;
[0063] Figure 8 is a flow chart of the preparation of the pole piece provided in the embodiment of the present application;
[0064] Fig. 9 It is a schematic diagram of the structure of a battery provided in an embodiment of the present application.
[0065] Fig.10 is a SEM image of the electrode provided in Example 8, in which A refers to the first active material layer and B refers to the conductive layer;
[0066] Fig.11 yes Fig.10 Enlarged SEM image of the framed part;
[0067] Fig.12 is a SEM image of the electrode provided in Example 1, in which A refers to the first active material layer and B refers to the conductive layer;
[0068] Fig.13 yes Fig.12 Enlarged SEM image of the framed part;
[0069] Fig.14 is a SEM image of the pole piece provided in Comparative Example 1;
[0070] Fig.15 The following are photos of the surface cleanliness test of the electrode samples at different preparation stages provided in Example 8, wherein: Fig.15 (a) shows a sample surface cleanliness test photograph before etching the active material layer; Fig.15 (b) shows a photo of the sample surface cleanliness test after the active material layer is etched; Fig.15 Figure (c) shows a photo of the surface cleanliness test of the sample after coating the conductive layer;
[0071] Fig.16 (a) is a photo of the electrode and the diaphragm provided in Example 1 after the electrode and the diaphragm are wound and then separated; Fig.16Figure (b) shows a photograph of the electrode sheet and the diaphragm provided in Example 8 after the electrode sheet and the diaphragm are wound and then separated; Fig.16 Figure (c) shows a comparison of two diaphragms. The upper diaphragm in the figure is the diaphragm wound around the pole piece provided in Comparative Example 1, and the lower diaphragm in the figure is the diaphragm wound around the pole piece provided in Example 8.
[0072] Reference numerals:
[0073] 10. Pole piece;
[0074] 1. Current collector;
[0075] 2. Composite layer;
[0076] 21, first active material layer; 211, first surface; 212, recess; 21a, second wet film layer;
[0077] 22, liquid absorption layer; 22a, first wet film layer;
[0078] 23, second active material layer; 23a, third wet film layer;
[0079] 100.Battery. DETAILED DESCRIPTION
[0080] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of this application.
[0081] In addition, it should be understood that the specific embodiments described herein are only used to illustrate and explain the present application, and are not used to limit the present application. In the present application, unless otherwise stated, the directional words used, such as "upper" and "lower", generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device.
[0082] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0083] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or mutual communication; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0084] The terms "comprises," "includes," or any other variation thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements, but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus. In the absence of further limitations, an element defined by the phrase "comprises a ..." does not exclude the presence of additional identical elements in the process, method, article, or apparatus that includes the element.
[0085] In the description of the embodiments of the present application, words such as "example" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "example" or "for example" in the embodiments of the present application is not to be interpreted as being more preferred or having more advantages than another embodiment or design. The use of words such as "example" or "for example" is intended to present relative concepts in a clear manner.
[0086] To facilitate understanding of the scheme of the present application, the spline curves and arrows used in the drawings are explained here: the components indicated by the spline curves without arrows are solid components, that is, components with solid structures; the components indicated by the spline curves with arrows are virtual components, that is, components without solid structures.
[0087] The embodiments of the present application provide a pole piece, a method for preparing a pole piece, and a battery, and the embodiments are described in detail below.
[0088] First, see Figures 1 to 7 The embodiment of the present application provides a pole piece 10, which includes a current collector 1 and a composite layer 2, and the composite layer 2 is arranged on the current collector 1. The composite layer 2 includes a first active material layer 21 and a liquid absorption layer 22 arranged in sequence in a direction away from the current collector 1, the first active material layer 21 has a first surface 211 away from the current collector 1, and a concave portion 212 extending from the first surface 211 to the inside of the first active material layer 21 is also formed on the first active material layer 21, and the liquid absorption layer 22 covers the first surface 211 and the inner surface of the concave portion 212.
[0089] The electrode sheet 10 can be applied to a battery 100, such as a secondary battery, including but not limited to a lithium-ion battery. The electrode sheet 10 can be a positive electrode sheet or a negative electrode sheet. When the electrode sheet 10 is a positive electrode sheet, the current collector 1 is a positive electrode current collector, and the first active material layer 21 is a positive electrode active material layer; when the electrode sheet 10 is a negative electrode sheet, the current collector 1 is a negative electrode current collector, and the first active material layer 21 is a negative electrode active material layer.
[0090] If the current collector 1 is a positive electrode current collector, as an example, the current collector 1 can be aluminum foil, carbon-coated aluminum foil, safety-primed aluminum foil, etched aluminum foil or aluminum mesh. The thickness of the current collector 1 can be 5 μm to 20 μm, for example 5 μm, 10 μm, 15 μm or 20 μm.
[0091] If the current collector 1 is a negative electrode current collector, as an example, the current collector 1 can be a copper foil having a thickness of 3 μm to 20 μm, for example, 3 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm or 20 μm.
[0092] The current collector 1 has two opposite surfaces along the thickness direction of the current collector 1 . The composite layer 2 is arranged on the current collector 1 . The composite layer 2 may be combined with one surface of the current collector 1 or with both surfaces of the current collector 1 .
[0093] The composite layer 2 includes a first active material layer 21 and a liquid absorption layer 22 combined together, and the first active material layer 21 and the liquid absorption layer 22 are distributed in sequence along the direction away from the current collector 1, that is, the first active material layer 21 is located between the current collector 1 and the liquid absorption layer 22, and the first active material layer 21 is closer to the current collector 1 than the liquid absorption layer 22.
[0094] For the convenience of subsequent distinction, the surface of the first active material layer 21 that is away from the current collector 1 (in other words, close to the liquid absorption layer 22 ) is referred to as the first surface 211 .
[0095] Among them, the side of the first active material layer 21 away from the current collector 1 is concave-convex, specifically, a concave portion 212 is provided on the first active material layer 21, and the concave portion 212 is formed by the first active material layer 21 being partially concave from the first surface 211 to the inside of the first active material layer 21, that is, the opening of the concave portion 212 is located on the first surface 211 (that is, the opening faces outward), and the concave portion 212 extends to the inside of the first active material layer 21. Usually, there are some undepressed positions on the first active material layer 21, and this part is formed as a convex portion, so that the side of the first active material layer 21 away from the current collector 1 presents a concave-convex structure. As an example, the concave portion 212 includes at least one of a groove and a through hole. Optionally, the groove includes a blind hole. Here, the formation method of the concave portion 212 includes but is not limited to at least one of laser etching, layered coating, and pore-forming agent pore formation.
[0096] The first active material layer 21 and the liquid absorbing layer 22 are combined together. Specifically, the liquid absorbing layer 22 covers the first surface 211 and extends into the concave portion 212 to cover the inner surface of the concave portion 212. The liquid absorbing layer 22 extends into the concave portion 212, and the liquid absorbing layer 22 can fill the concave portion 212. Figure 2 For example, when the liquid-absorbing layer 22 is thicker or the concave portion 212 is narrower or the concave portion 212 is shallower, the liquid-absorbing layer 22 is more likely to fill the concave portion 212; it may be that the liquid-absorbing layer 22 is only attached to the inner surface of the concave portion 212 and does not completely fill the concave portion 212, see Figure 1 For example, when the liquid-absorbing layer 22 is thinner or the recess 212 is wider or deeper, the liquid-absorbing layer 22 is more likely to be attached to the inner surface of the recess 212. The inner surface of the recess 212 refers to the inner wall surface of the recess 212, including the bottom wall surface and the side wall surface.
[0097] The first active material layer 21 is a layer structure including at least an active material. Optionally, the first active material layer 21 also includes a binder and a conductive agent. For the convenience of subsequent description, the active material, binder and conductive agent in the first active material layer 21 are respectively referred to as the first active material, the second binder and the second conductive agent. When the types of the first active material layer 21 are different, the selection of the first active material, the second binder and the second conductive agent contained therein will also be different. In some embodiments, the first active material layer 21 may not include a conductive agent, that is, a conductive agent-free formula design.
[0098] If the first active material layer 21 is a positive electrode active material layer, the first active material is a positive electrode active material. As an example, the first active material includes at least one of nickel cobalt manganese ternary material (NMC), lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4, LFP), lithium manganese oxide (LiMn2O4, LMO) and nickel cobalt aluminum oxide (NCA). Similarly, the second conductive agent is a positive electrode conductive agent. As an example, the second conductive agent includes at least one of carbon black, conductive graphite, graphene and carbon nanotubes. Similarly, the second binder is a positive electrode binder, and the second binder includes at least one of organic polymers such as polyacrylic acid (PAA) and polyvinylidene fluoride (PVDF).
[0099] If the first active material layer 21 is a negative electrode active material layer, the first active material is a negative electrode active material, and as an example, the first active material includes at least one of graphite, graphene, hard carbon, soft carbon, and silicon-based materials. Similarly, the second conductive agent is a negative electrode conductive agent, and as an example, the second conductive agent includes at least one of carbon black, graphene, acetylene black, carbon nanotubes, and conductive graphite. Similarly, the second binder is a negative electrode binder, and as an example, the second binder includes styrene butadiene rubber (SBR).
[0100] The liquid absorption layer 22 refers to a structural layer that has a better absorption capacity for electrolyte, specifically, the ability of the liquid absorption layer 22 to absorb electrolyte (abbreviated as liquid absorption) is at least better than the ability of the first active material layer 21 to absorb electrolyte. Here, the amount of electrolyte absorbed by a unit volume of material per unit time can be used to indicate the ability of the material to absorb electrolyte; generally, the larger the amount of electrolyte, the better the ability of the material to absorb electrolyte. The time taken for a unit volume of material to absorb a unit volume of electrolyte can also be used to indicate the ability of the material to absorb electrolyte; generally, the shorter the time, the better the ability of the material to absorb electrolyte. For example, the absorption capacity of the liquid absorption layer 22 and the first active material layer 21 for electrolyte can be tested by contact angle testing. Generally, the time for the same volume of electrolyte to completely enter the liquid absorption layer 22 is shorter than the time for it to completely enter the first active material layer 21.
[0101] The pole piece 10 provided in the embodiment of the present application includes a current collector 1 and a first active material layer 21, a concave portion 212 is formed on the first active material layer 21, the opening of the concave portion 212 faces outward but the concave portion 212 extends toward the inside of the first active material layer 21, and the pole piece 10 also includes a liquid absorption layer 22, the liquid absorption layer 22 is combined with the first active material layer 21 and covers the first surface 211 of the first active material layer 21 and the inner surface of the concave portion 212, compared with the first active material layer 21, because the liquid absorption layer 22 has a better The electrolyte can be absorbed by the liquid absorption layer 22 in the concave portion 212, so that the electrolyte can be preferentially penetrated into the first active material layer 21 through the portion of the liquid absorption layer 22 located in the concave portion 212, shortening the transmission path of lithium ions, improving the infiltration effect of the electrolyte on the pole piece 10, and increasing the probability of the active material particles in the pole piece 10 contacting with the electrolyte; and the liquid absorption layer 22 can also be used as an electrolyte carrier to store the electrolyte, so that during the charge and discharge process of the pole piece 10, the electrolyte stored in the liquid absorption layer 22 can be quickly supplied to the first active material layer 21. Therefore, when the liquid absorption layer 22 is located on the inner surface of the concave portion 212, the liquid absorption layer 22 cooperates with the concave portion 212 and forms a "fast channel", so that the electrolyte can quickly enter the first active material layer 21, promote the transmission of lithium ions in the pole piece 10 and increase the migration speed of lithium ions, and reduce the concentration polarization inside the pole piece 10.
[0102] In some embodiments, in the first active material layer 21, the first active material is in granular form, i.e., first active material particles. Thus, structurally, the first active material layer 21 includes: a first base layer having a second binder and a second conductive agent, and first active material particles dispersed in the first base layer.
[0103] As an example, the liquid absorption capacity of the liquid absorption layer 22 can be improved by adjusting the composition and structure of the liquid absorption layer 22.
[0104] In some embodiments, see Figure 1 The liquid absorbing layer 22 is a mixed layer including at least a first adhesive and a first conductive agent.
[0105] It can be understood that the liquid absorbing layer 22 also includes a binder and a conductive agent. For the convenience of description, the binder and the conductive agent in the liquid absorbing layer 22 are respectively referred to as the first binder and the first conductive agent. The liquid absorbing layer 22 includes a first binder and a first conductive agent. The first binder can combine the liquid absorbing layer 22 with the first active material layer 21, and the first conductive agent can make the liquid absorbing layer 22 have a certain conductivity, which not only facilitates the transmission of current between the liquid absorbing layer 22 and the first active material layer 21, but also reduces the internal resistance of the pole piece 10. Generally, the conductive agent has a strong ability to absorb electrolyte. Adding the first conductive agent to the liquid absorbing layer 22 can also enhance the ability of the liquid absorbing layer 22 to infiltrate the electrolyte. The first binder and the second binder can be the same or different. The first conductive agent and the second conductive agent can be the same or different. As an example, the first binder includes at least one of organic polymer materials such as carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE) and styrene-butadiene rubber (SBR). As an example, the first conductive agent includes at least one of a conductive carbon material and a conductive ceramic. Optionally, the conductive carbon material includes at least one of carbon black, carbon nanotubes, carbon fibers, acetylene black, graphite and graphene. Optionally, the carbon black includes at least one of conductive carbon black Super P, superconducting carbon black and Ketjen black. Optionally, the carbon nanotubes include at least one of single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs). Optionally, the conductive ceramic includes at least one of CaF2 structured materials such as β-Al2O3, CaO·ZrO2 and Y2O3·ZrO2. In the liquid absorbing layer 22, the first binder and the first conductive agent are mixed together. Among them, the liquid absorbing layer 22 may contain active materials or may not contain active materials. When the liquid absorbing layer 22 contains active materials, the liquid absorbing layer 22 is formed as an active material layer; when the liquid absorbing layer 22 does not contain active materials, the liquid absorbing layer 22 is formed as a conductive layer.
[0106] In some embodiments, the first active material layer 21 is a mixed layer including a first active material, a second binder, and a second conductive agent. The first active material in the first active material layer 21 can improve the energy density of the electrode 10, the second binder can realize the bonding of the first active material layer 21 to the current collector 1, and the second conductive agent is dispersed in the first active material layer 21 to construct a conductive network to promote the transmission of ions.
[0107] In some embodiments, the mass content of the second conductive agent in the first active material layer 21 is less than the mass content of the first conductive agent in the liquid absorbing layer 22. Compared with the active material, the conductive agent generally has a better liquid absorption capacity. By increasing the mass content of the conductive agent (referred to as the first conductive agent) in the liquid absorbing layer 22, the liquid absorption capacity of the liquid absorbing layer 22 can be improved.
[0108] In some embodiments, the content of the first active material in the first active material layer 21 is greater than 50wt%, and the content of the first conductive agent in the liquid absorbing layer 22 is greater than 50wt%. It can be understood that the content of the second conductive agent in the first active material layer 21 is less than 50wt%, that is, the mass content of the first conductive agent in the liquid absorbing layer 22 is greater than the mass content of the second conductive agent in the first active material layer 21, thereby improving the liquid absorbing capacity of the liquid absorbing layer 22. As an example, the content of the first active material in the first active material layer 21 is 50wt%, 60wt%, 70wt%, 80wt%, 85wt%, 90wt%, 92wt%, 94wt%, 95wt%, 96wt%, 97wt% or 98wt%. As an example, the content of the first conductive agent in the liquid absorption layer 22 is 50wt%, 60wt%, 70wt%, 80wt%, 85wt%, 90wt%, 92wt%, 94wt%, 95wt%, 96wt%, 97wt%, 98wt% or 99wt%.
[0109] In some embodiments, the first active material layer 21 includes a first active material, and the oil absorption value of the first conductive agent is greater than the oil absorption value of the first active material. Since the electrolyte mainly includes electrolytes and organic solvents, the ability of the liquid absorbing layer 22 to absorb the electrolyte can be improved by increasing the oil absorption value of the first conductive agent in the liquid absorbing layer 22, that is, the electrolyte is more easily absorbed by the liquid absorbing layer 22 than the first active material layer 21. Optionally, the liquid absorbing layer 22 does not contain an active material or contains a small amount of active material.
[0110] In some embodiments, the porosity of the liquid absorbing layer 22 is at least greater than the porosity of the first active material layer 21. By increasing the porosity of the liquid absorbing layer 22, the liquid absorbing capacity of the liquid absorbing layer 22 can also be improved. In this case, the liquid absorbing layer 22 can be an active material layer or a conductive layer. When the liquid absorbing layer 22 is an active material layer, the amount of active material in the liquid absorbing layer 22 can be more or less.
[0111] When the liquid absorbing layer 22 also contains active materials, for the convenience of description, the active material in the liquid absorbing layer 22 is referred to as the third active material. The third active material may be the same as or different from the first active material. However, the porosity of the liquid absorbing layer 22 is greater than the porosity of the first active material layer 21. Ways to adjust the porosity of the liquid absorbing layer 22 include, but are not limited to, selecting a material with a lower compaction density, increasing the particle size of the material, reducing the compaction density of the liquid absorbing layer 22, and the like. For example, when preparing the first active material layer 21, the first active material layer 21 is first subjected to a roller pressing treatment, and when preparing the liquid absorbing layer 22, no roller pressing treatment is performed. Similarly, when the pole piece 10 is a positive pole piece, the liquid absorbing layer 22 is a positive active material layer; when the pole piece 10 is a negative pole piece, the liquid absorbing layer 22 is a negative active material layer. When the type of the liquid absorbing layer 22 is different, the selection of the third active material contained therein will also be different.
[0112] If the liquid absorption layer 22 is a positive electrode active material layer, the third active material is a positive electrode active material. As an example, the third active material includes at least one of nickel cobalt manganese ternary material (NMC), lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4, LFP), lithium manganese oxide (LiMn2O4, LMO) and nickel cobalt aluminum oxide (NCA). If the liquid absorption layer 22 is a negative electrode active material layer, the third active material is a negative electrode active material. As an example, the third active material includes at least one of graphite, graphene, hard carbon, soft carbon and silicon-based materials. In some embodiments, when the liquid absorption layer 22 is an active material layer, the third active material is granular, that is, third active material particles. In this way, in terms of structure, the liquid absorption layer 22 includes: a third base layer having a first binder and a first conductive agent, and third active material particles dispersed in the third base layer.
[0113] In some embodiments, the recess 212 is a laser-etched portion, that is, the recess 212 is obtained by locally irradiating the first active material layer 21 with a high-energy-density laser beam, so that the material in the local area of the first active material layer 21 is vaporized and evaporated in a very short time. The preparation of the recess 212 by laser etching is not only efficient, but also easy to control the shape and size of the recess 212. However, the preparation of the recess 212 by laser etching will cause micron-level dust to remain on the surface of the first active material layer 21 (especially the inner surface of the recess 212). These dusts mainly come from the loosened first active material and the second conductive agent and the carbonized second binder, and these micron-level dusts are difficult to remove by dust removal equipment, so when the pole piece 10 is used to prepare the battery 100, these dusts are easily brought into the diaphragm of the battery 100 through the electrolyte, thereby causing the internal short circuit of the battery 100 or the increase of self-discharge. However, in the embodiment of the present application, since the pole piece 10 also includes a liquid absorption layer 22, the liquid absorption layer 22 is combined with the first active material layer 21 and covers the first surface 211 of the first active material layer 21 and the inner surface of the recess 212. The liquid absorption layer 22 can cover the dust remaining on the surface of the first active material layer 21 to prevent the dust from entering the electrolyte, and the binder (referred to as the first binder) contained in the liquid absorption layer 22 can also stick to the dust, especially on the inner surface of the recess 212. The binder will penetrate into the first active material layer 21 in small amounts to form a bonding interface layer between the liquid absorption layer 22 and the first active material layer 21. Not only will a large amount of dust be solidified in the bonding interface layer, but the bonding interface layer can also prevent the loose material on the side wall of the recess 212 from further loosening, thereby ultimately reducing the dust from detaching from the pole piece 10 and reducing the risk of internal short circuit or increased self-discharge of the battery 100.
[0114] In some embodiments, the specific surface area of the first conductive agent is 1 m 2 / g~1000m 2 / g. The specific surface area of the first conductive agent will affect the ability of the liquid absorbing layer 22 to store electrolyte. The larger the specific surface area of the first conductive agent, the stronger the ability of the liquid absorbing layer 22 to store electrolyte. As an example, the specific surface area of the first conductive agent is 1m 2 / g, 10m 2 / g、100m 2 / g, 200m 2 / g、300m 2 / g, 400m 2 / g、500m 2 / g、600m 2 / g、700m 2 / g、800m 2 / g、900m 2 / g or 1000m 2 / g. It is usually related to the specific surface area of the first conductive agent and the morphology of the material. As an example, the first conductive agent includes a conductive carbon material, and the conductive carbon material includes at least one of carbon black, carbon nanotubes, carbon fibers, graphite and graphene, wherein the specific surface area of carbon black is greater than 5m 2 / g, the specific surface area of carbon nanotubes is greater than 1m 2 / g, the specific surface area of graphene is 1m 2 / g~500m 2 / g, the specific surface area of graphite is 1m 2 / g~1000m 2 / g, the specific surface area of carbon fiber is 1m 2 / g~1000m 2 / g.
[0115] In some embodiments, the D50 particle size (i.e., average particle size) of the first conductive agent is 1 nm to 50 μm. The larger the D50 particle size of the first conductive agent, the greater the porosity of the liquid absorbing layer 22, so that the liquid storage space of the liquid absorbing layer 22 is increased, and the electrolyte is more likely to penetrate the liquid absorbing layer 22 to reach the first active material layer 21. However, if the D50 particle size of the first conductive agent is too large, it will affect the thickness of the liquid absorbing layer 22, and the D50 particle size of the first conductive agent is too large, which is easy to reduce the specific surface area of the first conductive agent. As an example, the D50 particle size of the first conductive agent is 1 nm, 5 nm, 10 nm, 100 nm, 200 nm, 500 nm, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm or 50 μm. As an example, the first conductive agent includes a conductive carbon material, and the conductive carbon material includes at least one of carbon black, carbon nanotubes, carbon fibers, graphite and graphene, wherein the D50 particle size of carbon black is 1nm to 200nm, the D50 particle size of carbon nanotubes is 1nm to 100nm, the D50 particle size of graphene is 1μm to 50μm, the D50 particle size of graphite is 10nm to 20μm, and the D50 particle size of carbon fiber is 5nm to 1μm.
[0116] In some embodiments, the first conductive agent has an oil absorption value greater than that of the first active material.
[0117] In some embodiments, the oil absorption value of the first conductive agent is greater than or equal to 500mL / 100g. Usually, the solvent in the electrolyte is an organic solvent, and the oil absorption value of the first conductive agent will affect the ability of the liquid absorption layer 22 to absorb the electrolyte. By setting the oil absorption value of the first conductive agent to be greater than or equal to 500mL / 100g, the liquid absorption layer 22 can be quickly infiltrated with the electrolyte, thereby accelerating the electrolyte to enter the interior of the electrode 10. As an example, the oil absorption value of the first conductive agent is 500mL / 100g, 1000mL / 100g, 1500mL / 100g, 2000mL / 100g or 2500mL / 100g. As an example, the first conductive agent includes conductive carbon black, and the oil absorption value of the conductive carbon black is 1000mL / 100g; or the first conductive agent includes carbon nanotubes, and the oil absorption value of the carbon nanotubes is 500mL / 100g; or the first conductive agent includes graphene, and the oil absorption value of the graphene is 2000mL / 100g; or the first conductive agent includes graphite, and the oil absorption value of the graphite is 500mL / 100g.
[0118] In some embodiments, the conductivity of the first conductive agent is 3000S·cm to 12000S·cm. The greater the conductivity of the first conductive agent, the greater the conductivity of the liquid absorption layer 22, which is beneficial to reduce the internal resistance of the battery 100. As an example, the conductivity of the first conductive agent is 3000S·cm, 5000S·cm, 7000S·cm, 9000S·cm, 10000S·cm or 12000S·cm. As an example, the first conductive agent includes carbon black, and the conductivity of carbon black is 3000S·cm; or the first conductive agent includes carbon nanotubes, and the conductivity of carbon nanotubes is 5000S·cm; or the first conductive agent includes graphene, and the conductivity of graphene is 12000S·cm; or the first conductive agent includes graphite, and the conductivity of graphite is 5000S·cm; or the first conductive agent includes carbon fiber, and the conductivity of carbon fiber is 5000S·cm.
[0119] In some embodiments, the liquid absorbing layer 22 includes 1 wt% to 80 wt% of the first conductive agent, 10 wt% to 99 wt% of the first binder, and the liquid absorbing layer 22 also includes 0 wt% to 30 wt% of the dispersant. That is, the liquid absorbing layer 22 is a conductive layer, that is, the liquid absorbing layer 22 does not contain active materials, and the liquid absorbing layer 22 mainly includes a conductive agent and a binder, for example, the liquid absorbing layer 22 only includes the first conductive agent and the first binder, or the liquid absorbing layer 22 only includes the first conductive agent, the first binder and the dispersant. Within the above range, the protective layer 3 is a conductive layer, and the liquid absorbing layer 22 has both good liquid absorption capacity and bonding stability with the first active material layer 21, especially when the concave portion 212 is a laser etched portion, the first binder can better penetrate into the active material layer 2 from the inner wall surface of the concave portion 212, and better solidify the inner wall of the concave portion 212, thereby effectively reducing the floating powder of the electrode 10. As an example, the content of the first conductive agent is 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt% or 80wt%; the content of the first binder is 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt% or 99wt%; the content of the dispersant is 0wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt% or 30wt%. When the liquid absorbing layer 22 also includes a dispersant, the dispersant can effectively promote the dispersion of the first conductive agent in the first binder, especially when the first conductive agent is a conductive carbon material. Optionally, the dispersant is at least one of an ionic dispersant, a nonionic dispersant and a polymer dispersant. As an example, the dispersant includes at least one of anhydride, polyvinyl pyrrolidone (PVP), sulfate, sulfonate, poly (N-vinyl acetamide) (PNVA), polyvinyl alcohol (PVA) and polyethylene glycol. In the liquid absorbing layer 22, the first binder, the first conductive agent and the dispersant are mixed together.
[0120] In some embodiments, the liquid absorbing layer 22 includes 58wt% to 75wt% of the first conductive agent, 12.5wt% to 30wt% of the first binder, and 8wt% to 12.5wt% of the dispersant. Within the above range, the liquid absorbing layer 22 has both good liquid absorption capacity and bonding stability, effectively reducing the floating powder of the pole piece 10. As an example, in the protective layer 3, the content of the first conductive agent is 58wt%, 60wt%, 62wt%, 64wt%, 66wt%, 68wt%, 70wt%, 72wt%, 74wt% or 75wt%; the content of the first binder is 12.5wt%, 14wt%, 16wt%, 18wt%, 20wt%, 22wt%, 24wt%, 26wt%, 28wt% or 30wt%; the content of the dispersant is 8wt%, 9wt%, 10wt%, 11wt%, 12wt% or 12.5wt%.
[0121] In some embodiments, the porosity of the liquid absorbent layer 22 is 5% to 99%. The greater the porosity of the liquid absorbent layer 22, the greater the liquid storage capacity of the liquid absorbent layer 22. As an example, the porosity of the liquid absorbent layer 22 is 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or 99%.
[0122] In some embodiments, the thickness of the liquid absorbing layer 22 is 0.2 μm to 50 μm. Generally, the thicker the liquid absorbing layer 22 is, the greater the amount of liquid absorbed by the liquid absorbing layer 22 is, and the rate performance of the battery 100 is improved. However, if the liquid absorbing layer 22 is too thick, the energy density of the battery 100 will also decrease. As an example, the thickness of the liquid absorbing layer 22 is 0.2 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm. Here, the thickness of the liquid absorbing layer 22 is an average thickness.
[0123] In some embodiments, the thickness of the liquid absorbing layer 22 is 0.2 μm to 10 μm. When the thickness of the liquid absorbing layer 22 is within this range, the battery 100 has both good rate performance and energy density. As an example, the thickness of the liquid absorbing layer 22 is 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm. Here, the thickness of the liquid absorbing layer 22 is an average thickness.
[0124] In some embodiments, the pole piece 10 is a thick pole piece, wherein the thickness of the first active material layer 21 is greater than 30 μm. By increasing the thickness of the first active material layer 21, the content of active material in the pole piece 10 is increased, thereby increasing the energy density of the battery 100. As an example, the thickness of the first active material layer 21 is 31 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm or 150 μm.
[0125] In some embodiments, the pole piece 10 is a thick pole piece, the current collector 1 is provided with the composite layer 2 only on one side, and the thickness of the pole piece 10 is greater than 60 μm. As an example, the thickness of the pole piece 10 is 61 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 130 μm, 150 μm, 170 μm, 190 μm or 210 μm.
[0126] In some embodiments, the pole piece 10 is a thick pole piece, but the composite layer 2 is provided on both sides of the current collector 1, and the thickness of the pole piece 10 is greater than 60 μm. As an example, the thickness of the pole piece 10 is 61 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 170 μm, 190 μm, 210 μm, 250 μm, 280 μm or 300 μm.
[0127] In some embodiments, see Figure 7 , the concave portion 212 is a long strip-shaped groove, the groove extends along the first direction of the first active material layer 21, and the length H1 of the groove extending in the first direction is less than or equal to the length H2 of the first active material layer 21 in the first direction. For example, the first direction may be the transverse direction (TD direction) or the longitudinal direction (MD direction) of the first active material layer 21. As an example, the first direction is the X direction, the groove extends along the X direction on the first active material layer 21, and the length H1 of the groove is equal to the length H2 of the first active material layer 21. As an example, the first direction is the X direction, the groove extends along the X direction on the first active material layer 21, and the length H1 of the groove is less than the length H2 of the first active material layer 21. In other cases, the first direction may also be the Y direction.
[0128] In some embodiments, the number of recesses 212 is multiple, and the multiple recesses 212 are spaced apart. By increasing the number of recesses 212 provided on the first active material layer 21, and distributing the multiple recesses 212 at intervals, that is, the multiple recesses 212 are dispersed on the first active material layer 21, it is beneficial to improve the overall liquid absorption effect of the first active material layer 21 and reduce the concentration polarization inside the pole piece 10. Optionally, the spacing between two adjacent recesses 212 is 0.01 mm to 100 mm. The spacing between two adjacent recesses 212 should not be too large, otherwise the number of recesses 212 that can be provided per unit area will be reduced. As an example, it is 0.01 mm, 0.1 mm, 1 mm, 10 mm, 20 mm, 30 mm, 40 mm, 50 mm, 60 mm, 70 mm, 80 mm, 90 mm or 100 mm. As an example, see Figure 7 The distance between two adjacent recesses 212 may refer to a distance W1 between two adjacent recesses 212 in the lateral direction of the first active material layer 21 , or may refer to a distance W2 between two adjacent recesses 212 in the longitudinal direction of the first active material layer 21 .
[0129] In some embodiments, the width of the recess 212 remains unchanged or decreases along the direction close to the current collector 1. In this way, the width of the recess 212 is the largest at the opening, which is not only beneficial to the manufacture of the recess 212 itself, but also beneficial to make the liquid absorbing layer 22 extend into the recess 212 and combine with the inner surface of the recess 212 when manufacturing the liquid absorbing layer 22.
[0130] In some embodiments, the sidewall of the recess 212 may be a straight wall or a curved wall. As an example, the sidewall of the recess 212 is an arc-shaped curved wall. When the sidewall of the recess 212 is a straight wall, the sidewall of the recess 212 may extend along the thickness direction of the first active material layer 21 or may be inclined relative to the thickness direction of the first active material layer 21.
[0131] In some embodiments, see Figure 6 When the concave portion 212 is cut along the thickness direction of the first active material layer 21 , the cross section of the concave portion 212 is V-shaped, trapezoidal, square, semicircular, or semi-elliptical.
[0132] In some embodiments, the average width of the recess 212 is 1 μm to 300 μm. The width of the recess 212 should not be too small, otherwise it is not conducive for the liquid absorption layer 22 to extend into the recess 212, but it should not be too large, otherwise the recess 212 will be too wide, resulting in insufficient mass proportion of the first active material layer 21 in the pole piece 10. As an example, the average width of the recess 212 is 1 μm, 5 μm, 10 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm or 300 μm.
[0133] In some embodiments, the depth of the recess 212 is less than the thickness of the first active material layer 21. Generally, in the pole piece 10, the first active material layer 21 closer to the current collector 1 is farther from the electrolyte, and is less likely to be infiltrated by the electrolyte, resulting in concentration polarization in the pole piece 10. The deeper the depth of the recess 212, the closer it is to the current collector 1, so that the electrolyte is more likely to quickly penetrate into the portion of the first active material layer 21 close to the current collector 1 through the recess 212, thereby reducing the concentration polarization in the pole piece 10. Optionally, the depth of the recess 212 is greater than half the thickness of the first active material layer 21. As an example, the ratio of the depth of the recess 212 to the thickness of the first active material layer 21 is 0.5, 0.6, 0.7, 0.8, 0.9, 0.95 or 0.98.
[0134] In some embodiments, the content of the second conductive agent in the first active material layer 21 increases along the direction close to the current collector 1. In the first active material layer 21, the second conductive agent has a better wetting effect on the electrolyte than the first active material. By increasing the content of the second conductive agent in the portion of the first active material layer 21 close to the current collector 1, it is beneficial to promote the rapid migration of lithium ions into the interior of the first active material layer 21, improve the uniformity of the first active material layer 21 infiltrating the electrolyte, and reduce the concentration polarization inside the first active material layer 21. As an example, see Figure 5 The first active material layer 21 includes a plurality of stacked sub-active material layers, and the content of the second conductive agent in each sub-active material layer gradually increases along a direction approaching the current collector 1 .
[0135] In some embodiments, in the first active material layer 21, the first active material is in a granular form, i.e., first active material particles, so that structurally, the first active material layer 21 is a mixed layer including first active material particles, a second binder, and a second conductive agent. In the first active material layer 21, the average particle size of the first active material particles increases along the direction close to the current collector 1. By increasing the average particle size of the first active material in the portion of the first active material layer 21 close to the current collector 1, the porosity of the portion of the first active material layer 21 close to the current collector 1 can be increased, which is beneficial to promote the migration of lithium ions into the interior of the first active material layer 21 through the pores, improve the uniformity of the electrolyte infiltrated into the first active material layer 21, and reduce the concentration polarization inside the first active material layer 21. As an example, see Figure 5 The first active material layer 21 includes a plurality of stacked sub-active material layers, and the average particle size of the first active material in each sub-active material layer gradually increases along a direction approaching the current collector 1 .
[0136] In some embodiments, see Figure 3The composite layer 2 further includes a second active material layer 23 , which is disposed on the surface of the liquid absorbing layer 22 and away from the first active material layer 21 .
[0137] Specifically, along the direction away from the current collector 1, the first active material layer 21, the liquid absorbing layer 22, and the second active material layer 23 are sequentially distributed, and the liquid absorbing layer 22 is sandwiched between the first active material layer 21 and the second active material layer 23. In the case where the liquid absorbing layer 22 does not fill the concave portion 212, the second active material layer 23 can be partially filled in the concave portion 212; in the case where the liquid absorbing layer 22 fills the concave portion 212, the second active material layer 23 is spread on one side surface of the liquid absorbing layer 22.
[0138] The second active material layer 23 also includes an active material and a binder. For ease of description, the active material and the binder in the second active material layer 23 are referred to as the second active material and the third binder, that is, the second active material layer 23 is a mixed layer including at least the second active material and the third binder. Optionally, the second active material layer 23 also includes a conductive agent, referred to as a third conductive agent. The second active material and the first active material may be the same or different, the third binder and the second binder may be the same or different, and the third conductive agent and the second conductive agent may be the same or different. The composition of the second active material layer 23 may be the same or different from that of the first active material layer 21.
[0139] Similarly, when the electrode sheet 10 is a positive electrode sheet, the second active material layer 23 is a positive electrode active material layer; when the electrode sheet 10 is a negative electrode sheet, the second active material layer 23 is a negative electrode active material layer. When the type of the second active material layer 23 is different, the selection of the second active material, the third binder and the third conductive agent contained therein will also be different.
[0140] If the second active material layer 23 is a positive electrode active material layer, the second active material is a positive electrode active material. As an example, the second active material includes at least one of nickel cobalt manganese ternary material (NMC), lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4, LFP), lithium manganese oxide (LiMn2O4, LMO) and nickel cobalt aluminum oxide (NCA). Similarly, the third conductive agent is a positive electrode conductive agent. As an example, the third conductive agent includes at least one of carbon black, conductive graphite, graphene, acetylene black, and carbon nanotubes. Similarly, the third binder is a positive electrode binder, and the third binder includes at least one of organic polymer materials such as polyacrylic acid (PAA) and polyvinylidene fluoride (PVDF).
[0141] If the second active material layer 23 is a negative electrode active material layer, the second active material is a negative electrode active material, and as an example, the second active material includes at least one of graphite, graphene, hard carbon, soft carbon, and silicon-based materials. Similarly, the third conductive agent is a negative electrode conductive agent, and as an example, the third conductive agent includes at least one of carbon black, graphene, acetylene black, carbon nanotubes, and conductive graphite. Similarly, the third binder is a negative electrode binder, and as an example, the third binder includes styrene butadiene rubber (SBR).
[0142] In the pole piece 10 provided in the embodiment of the present application, the composite layer 2 includes a first active material layer 21, a liquid absorbing layer 22 and a second active material layer 23. The first active material layer 21 and the second active material layer 23 serve together as active material layers, and the liquid absorbing layer 22 is sandwiched between the first active material layer 21 and the second active material layer 23, which is equivalent to the liquid absorbing layer 22 being arranged inside the active material layer. In this way, when the pole piece 10 is applied to the battery 100, when the battery 100 is not working (for example, when it is stationary), the electrolyte can be absorbed and preserved by utilizing the good wetting ability of the liquid absorbing layer 22. During the charge and discharge process of the battery 100, the liquid absorbing layer 22 can be used as a small electrolyte source to continuously transport electrolyte to the first active material layer 21 and the second active material layer 23 on both sides, which greatly shortens the movement path of lithium ions and reduces the concentration polarization inside the pole piece 10. In addition, adding the second active material layer 23 can also improve the energy density of the battery 100.
[0143] In some embodiments, in the second active material layer 23, the second active material is in granular form, i.e., second active material particles. Thus, structurally, the second active material layer 23 includes: a second matrix layer having a third binder and a third conductive agent, and second active material particles dispersed in the second matrix layer.
[0144] In some embodiments, see Figure 4 , the number of composite layers 2 on a single side of the current collector 1 is multiple layers, and the multiple composite layers 2 are stacked. As an example, the number of composite layers 2 on a single side of the current collector 1 is 2 layers, 3 layers, 4 layers or 5 layers. The single side of the current collector 1 refers to one of the two opposite sides of the current collector 1. The number of composite layers 2 on one side of the current collector 1 is multiple layers, and the composite layer 2 may or may not be provided on the other side of the current collector 1. If a composite layer 2 is provided, the number of composite layers 2 may be one or more layers. The number of composite layers 2 here refers to the number of composite layers 2 themselves, not the number of active material layers and liquid absorption layers 22 inside the composite layer 2. As an example, the number of composite layers 2 is 2 layers. It can be understood that when the composite layer 2 only includes the first active material layer 21 and the liquid absorption layer 22, on a single side of the current collector 1, the number of first active material layers 21 is 2 layers, and the number of liquid absorption layers 22 is 2 layers.
[0145] In the embodiment of the present application, a plurality of composite layers 2 are stacked on a single side of the current collector 1, so that in the obtained pole piece 10, at least a portion of the liquid absorption layer 22 will be located inside the active material layer, and the active material layer may include a plurality of first active material layers 21, or may include a plurality of first active material layers 21 and a plurality of second active material layers 23. In this way, when the pole piece 10 is applied to the battery 100, when the battery 100 is not working, the electrolyte can be absorbed and preserved by utilizing the good wetting ability of the liquid absorption layer 22, and during the charge and discharge process of the battery 100, the liquid absorption layer 22 can be used as a small electrolyte source to continuously transport electrolyte to the active material layer, greatly shortening the movement path of lithium ions and reducing the concentration polarization inside the pole piece 10. In addition, increasing the number of composite layers 2 can also improve the energy density of the battery 100.
[0146] Second, see Figure 8 The present application also provides a method for preparing a pole piece 10, comprising:
[0147] S01 . Prepare a first active material layer 21 on the current collector 1 . The first active material layer 21 has a first surface 211 away from the current collector 1 , and a recess 212 is formed on the first active material layer 21 , extending from the first surface 211 to the inside of the first active material layer 21 .
[0148] S02 , subjecting the first slurry to a film-forming process on the first surface 211 and the recessed portion 212 of the first active material layer 21 , to obtain a liquid absorbing layer 22 .
[0149] The preparation method of the electrode 10 provided in the embodiment of the present application is simple in process and easy to implement. When the prepared electrode 10 is used on the battery 100, the electrode 10 is easily infiltrated by the electrolyte in the battery 100, and the electrolyte can also quickly penetrate into the interior of the electrode 10 with the help of the recess 212 and the liquid absorption layer 22 on the electrode 10, thereby shortening the path of lithium ion transmission, reducing the concentration polarization inside the electrode 10, and improving the rate performance of the battery 100.
[0150] In some embodiments, see Figure 8 Middle (a) picture~ Figure 8 In the middle (d) figure, in step S01, the process of preparing the first active material layer 21 on the current collector 1 includes:
[0151] S011, performing film-forming treatment on the current collector 1 with the second slurry to obtain a first active material layer 21;
[0152] S012 , laser etching is performed on a part of the first active material layer 21 from a side of the first active material layer 21 away from the current collector to form a concave portion 212 .
[0153] By first preparing the first active material layer 21 and then laser etching the first active material layer 21 to obtain the concave portion 212 , not only is the efficiency high, but the shape and size of the concave portion 212 are also easy to control.
[0154] In some embodiments, the recessed portion 212 may be formed simultaneously during the process of forming the first active material layer 21. For example, the first active material layer 21 is prepared by a double-layer coating method, and the recessed portion 212 is formed on the first active material layer 21 during the process of forming the first active material layer 21. The recessed portion 212 is specifically a micropore.
[0155] In some embodiments, see Figure 8 Middle (b) picture~ Figure 8 In the middle (c) figure, in step S011, the second slurry is subjected to film-forming treatment on the current collector 1 to obtain the first active material layer 21, which includes:
[0156] S0111, coating a second slurry on the current collector 1 to obtain a second wet film layer 21a, wherein the second slurry includes a first active material, a second binder, a second conductive agent, and a second solvent;
[0157] S0112 , drying the second wet film layer 21 a to volatilize the second solvent, thereby obtaining the first active material layer 21 .
[0158] The above method for preparing the first active material layer 21 is simple and is conducive to controlling the production cost.
[0159] In some embodiments, in the process of preparing the first active material layer 21, the second slurry is coated on the current collector 1 by at least one of gravure coating, micro-gravure coating, spraying and electrostatic spinning technology. The first active material, the second binder and the second conductive agent are described in the first aspect. The second solvent can be selected according to the type of the prepared pole piece 10. As an example, when the pole piece 10 is a positive pole piece, the second solvent includes N-methylpyrrolidone (NMP), and when the pole piece 10 is a negative pole piece, the second solvent includes water.
[0160] In some embodiments, the second wet film layer 21a is dried in an oven. When the electrode 10 is a positive electrode, the drying temperature may be 40°C to 150°C; when the electrode 10 is a negative electrode, the drying temperature may be 20°C to 110°C.
[0161] In some embodiments, the first active material layer 21 may be prepared by layered coating. In this way, micropores exist in the first active material layer 21 prepared, and the concave portion 212 includes micropores.
[0162] In some embodiments, see Figure 8Middle (e) picture~ Figure 8 In the middle (f) figure, in step S02, the first slurry is subjected to film-forming treatment on the first surface 211 and the concave portion 212 of the first active material layer 21 to obtain the liquid absorbing layer 22, which includes:
[0163] S021, providing a first slurry, wherein the first slurry includes a first solvent, a first conductive agent, and a first binder;
[0164] S022, coating the first slurry on the first surface 211 and the inner surface of the concave portion 212 to obtain a first wet film layer 22a;
[0165] S023, drying the first wet film layer 22a to volatilize the first solvent, thereby obtaining the liquid absorbing layer 22.
[0166] When laser etching is used to prepare the recess 212, there will be floating powder (i.e., residual dust at the micron level) on the surface of the first active material layer 21. The first slurry is further coated on the first surface 211 of the first active material layer 21 and the inside of the recess 212 to obtain a first wet film layer 22a. The first slurry includes a first solvent, a first conductive agent, and a first binder. As a wet material, the first slurry has a certain fluidity. During this process, the first wet film layer 22a will not only cover the floating powder on the surface of the first active material layer 21, but also a small amount of the first slurry in the first wet film layer 22a will penetrate into the first active material layer 21. After that, the first slurry loses the first solvent after drying and solidifies to form a liquid absorption layer 22. In this way, the floating powder on the surface of the first active material layer 21 will also be solidified in the interface area where the liquid absorption layer 22 and the first active material layer 21 are combined, thereby reducing the dust from escaping from the electrode 10 and entering the electrolyte, reducing the risk of dust adhering to the diaphragm, and thereby reducing the risk of short circuit in the battery 100.
[0167] In some embodiments, the first slurry is coated in the first surface 211 and the concave portion 212 of the first active material layer 21 by a method including, but not limited to, at least one of gravure coating, micro-gravure coating, spraying, and electrostatic spinning techniques. Optionally, the first solvent includes at least one of water, N-methylpyrrolidone, ethylene glycol, and isopropanol. Optionally, the first binder includes at least one of carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and styrene-butadiene rubber (SBR). Optionally, the first conductive agent includes at least one of a conductive carbon material and a conductive ceramic. Optionally, the conductive carbon material includes at least one of carbon black, carbon nanotubes, carbon fibers, acetylene black, graphite, and graphene. Optionally, carbon black includes at least one of conductive carbon black Super P, superconducting carbon black, and Ketjen black. Optionally, carbon nanotubes include at least one of single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs).
[0168] In some embodiments, the content of the first solvent in the first slurry is 10wt% to 97wt%. The content of the first solvent in the first slurry will affect the forming effect of the first wet film layer 22a, and then affect the liquid absorbing layer 22. In the first slurry, if the content of the first solvent is too high, the first slurry will be easy to drip, and the first wet film layer 22a will be difficult to form, while if the content of the first solvent is too low, the first slurry will have insufficient fluidity, and the uniformity and continuity of the first wet film layer 22a will be affected. As an example, the content of the first solvent in the first slurry is 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt%, 95wt% or 97wt%.
[0169] In some embodiments, the solid content in the first slurry is 3wt% to 90wt%. The solid content in the first slurry refers to the total content of other substances except the first solvent. If the solid content in the first slurry is too high, the fluidity of the first slurry is insufficient, and if the solid content in the first slurry is too low, the first slurry is easy to drip. As an example, the solid content in the first slurry is 3wt%, 5wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt% or 90wt%.
[0170] In some embodiments, the viscosity of the first slurry is 10 cp to 15000 cp. The viscosity of the first slurry affects the thickness of the liquid absorbing layer 22. The smaller the viscosity of the first slurry, the thinner the liquid absorbing layer 22 is. The larger the viscosity of the first slurry, the thicker the liquid absorbing layer 22 is. As an example, the viscosity of the first slurry is 10 cp, 100 cp, 500 cp, 1000 cp, 2000 cp, 3000 cp, 5000 cp, 8000 cp, 10000 cp, 12000 cp or 15000 cp.
[0171] In some embodiments, the first slurry further includes a dispersant. The dispersant is beneficial to improving the dispersion effect of the first conductive agent in the first solvent. Optionally, the dispersant includes at least one of anhydride, polyvinyl pyrrolidone (PVP), sulfate ester salt, sulfonate, poly (N-vinyl acetamide) (PNVA), polyvinyl alcohol (PVA) and polyethylene glycol.
[0172] In some embodiments, based on the total mass of the first conductive agent, the first binder and the dispersant, the contents of the first conductive agent, the first binder and the dispersant are as follows: 1 wt% to 60 wt% of the first conductive agent, 10 wt% to 99 wt% of the first binder and 0 wt% to 30 wt% of the dispersant. As an example, the content of the first conductive agent is 1 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt% or 60 wt%; the content of the first binder is 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt%, 80 wt%, 90 wt% or 99 wt%; the content of the dispersant is 0 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt% or 30 wt%.
[0173] In some embodiments, the first slurry can be prepared by wet pulping. Specifically, the first solvent, the dispersant, and the first binder are prepared into a glue solution in a mixing device, and then the first conductive agent is added and mixed to prepare the first slurry. The mixing device here includes but is not limited to a stirrer, a ball mill, a high-speed disperser, a grinder, etc. Of course, in some embodiments, the first solvent and the first binder can also be prepared into a glue solution in a mixing device, and then the first conductive agent and the dispersant are added and mixed to prepare the first slurry.
[0174] In some embodiments, the first slurry may be prepared by dry mixing. Specifically, the first conductive agent, the first binder and the dispersant are first mixed evenly in a mixing device, and then the first solvent is added for mixing to prepare the first slurry. Of course, in some embodiments, the first binder and the first solvent may be prepared into a binder glue, and the first conductive agent and the dispersant are mixed evenly in a mixing device, and then the binder glue is added for mixing to prepare the first slurry.
[0175] In some embodiments, the liquid absorbing layer 22 is a conductive layer, and the first slurry includes a first solvent, a first conductive agent, and a first binder. As an example, the first wet film layer 22a can be dried in an oven, and the drying temperature can be 20°C to 130°C. As an example, the drying temperature is 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, or 130°C.
[0176] In some embodiments, see Figure 8 , the method for preparing the pole piece 10 further includes:
[0177] S03 . Preparing a second active material layer 23 on the surface of the liquid absorbing layer 22 .
[0178] In some embodiments, see Figure 8 Middle (g) picture~ Figure 8 In the middle (h) figure, the preparation process of the second active material layer 23 includes:
[0179] S031, coating a third slurry on a side of the liquid absorbing layer 22 away from the current collector 1 to obtain a third wet film layer 23a, wherein the third slurry includes a second active material, a third solvent, a third conductive agent and a third binder;
[0180] S032, drying the third wet film layer 23a to volatilize the third solvent, thereby obtaining a second active material layer.
[0181] In the above-mentioned process of preparing the second active material layer 23, the method of coating the third slurry on the liquid absorbing layer 22 includes but is not limited to at least one of gravure coating, micro-gravure coating, spraying and electrostatic spinning technology. The second active material, the third conductive agent and the third binder are described in the first aspect. The third solvent can be selected according to the type of the prepared pole piece 10. As an example, when the pole piece 10 is a positive pole piece, the third solvent includes N-methylpyrrolidone (NMP), and when the pole piece 10 is a negative pole piece, the third solvent includes water.
[0182] As an example, the third wet film layer 23a can be dried in an oven. When the pole piece 10 is a positive pole piece, the drying temperature can be 40°C to 150°C; when the pole piece 10 is a negative pole piece, the drying temperature can be 20°C to 110°C.
[0183] Third, see Fig. 9 The embodiment of the present application further provides a battery 100 , which includes the above-mentioned electrode 10 .
[0184] The following is a description with reference to specific embodiments.
[0185] Example 1
[0186] S1. Preparation of electrode slurry (dry mixing): First, 12g of binder CMC was mixed with 738g of water to prepare glue solution, 960g of active material graphite and 13g of conductive agent conductive carbon black Super P (SP for short) were taken, the above materials were ground and mixed, 262.5g of glue solution and 234g of water were added for kneading, and then 487.5g of glue solution and 203.3g of water were added for stirring, and finally 37.5g of SBR was added to obtain an electrode slurry with a solid content of 45.5wt%. The current collector is copper foil, and the thickness of the current collector is 6um.
[0187] S2. Preparation of active material layer: coating the electrode slurry on the current collector by slot-die coating, drying the electrode sheet in an oven, curing the electrode slurry to form an active material layer, and performing roller pressing;
[0188] S3, etching grooves: etching grooves on the active material layer by laser etching, the power of the laser etching is 10W;
[0189] S4. Prepare conductive slurry: grind and mix 58g conductive carbon black, 30g CMC+SBR in total, and 12g PVP, then add into 85g water to prepare conductive slurry with a viscosity of 71cp.
[0190] S5. Prepare a conductive layer: apply a conductive slurry on the active material layer obtained in step S3 by gravure coating, dry the electrode after passing through an oven, and solidify the conductive slurry to form a conductive layer.
[0191] Example 2
[0192] The only difference from Example 1 is S4: Preparation of conductive slurry: 62 g of conductive carbon black, 28 g of CMC+SBR in total, and 10 g of PVP were ground and mixed, and then added into 83 g of water to prepare a conductive slurry with a viscosity of 76 cp.
[0193] Example 3
[0194] The only difference from Example 1 is S4: Preparation of conductive slurry: 66 g of conductive carbon black, 26 g of CMC+SBR in total, and 8 g of PVP were ground and mixed, and then added into 80 g of water to prepare a conductive slurry with a viscosity of 74 cp.
[0195] Example 4
[0196] The only difference from Example 2 is that the amount of water used in S4 is 87 g of water, and the viscosity of the prepared conductive paste is 63 cp.
[0197] Example 5
[0198] The only difference from Example 2 is that the amount of water used in S4 is 82 g of water, and the viscosity of the prepared conductive paste is 75 cp.
[0199] Example 6
[0200] The only difference from Example 2 is that the amount of water used in S4 is 76 g of water, and the viscosity of the prepared conductive paste is 89 cp.
[0201] Example 7
[0202] The only difference from Example 1 is S4: preparing a conductive paste: grinding and mixing 30 g of conductive carbon black, 5 g of PAA and 5 g of PVP, and adding them into 88 g of water to prepare a conductive paste with a viscosity of 25 cp.
[0203] Example 8
[0204] The only difference from Example 7 is that the amount of water used in S4 is 75 g of water, and the viscosity of the prepared conductive paste is 120 cp.
[0205] Comparative Example 1
[0206] The only difference from Embodiment 1 is that there are no steps S4 and S5.
[0207] The formula of the conductive paste in each example is shown in Table 1.
[0208] Table 1
[0209]
[0210] The pole piece samples provided in Examples 1 to 8 and Comparative Example 1 were characterized as follows:
[0211] 1. Measuring the thickness of the conductive layer: The thickness of the sample before and after the conductive layer is coated is measured by a micrometer, and the difference is taken to obtain the thickness of the conductive layer, and the results are recorded in Table 2. From the results in Table 2, it can be seen that when the viscosity of the conductive paste is similar (Examples 1 to 3 and 5), the thickness of the conductive layer obtained is similar, and as the solid content and viscosity of the conductive paste increase (Examples 4, 2, 5 and 6), the thickness of the conductive layer increases.
[0212] Table 2
[0213] Group Conductive layer thickness / μm Example 1 1.45 Example 2 1.45 Example 3 1.45 Example 4 0.85 Example 5 1.50 Example 6 2.60 Example 7 0.6 Example 8 3.15 Comparative Example 1 0
[0214] 2. Morphology characterization: Use argon ion precision cross-section cutting to cut the electrode cross section. After obtaining a flat cross section, use a scanning electron microscope (SEM) to observe the cross-sectional morphology and measure the thickness of the conductive layer.
[0215] like Fig.10 and Fig.11 Shown are SEM images of the electrode provided in Example 8 at different magnifications. It can be seen from the figure that the conductive layer covers the surface of the active material layer and fills the grooves on the active material layer. The average thickness of the portion of the conductive layer covering the surface of the active material layer is 2.91 μm, and the thickness of the portion of the conductive layer filling the grooves is 6.85 μm.
[0216] like Fig.12 and Fig.13Shown are SEM images of the electrode provided in Example 1 at different magnifications. It can be seen from the figure that the conductive layer also covers the surface of the active material layer and fills the grooves on the active material layer. The average thickness of the portion of the conductive layer covering the surface of the active material layer is 1.275 μm, and the thickness of the portion of the conductive layer filling the grooves is 2.85 μm.
[0217] like Fig.14 Shown is a SEM image of the electrode provided in Comparative Example 1. The area circled in the figure is the area where the active material layer is etched. It can be seen from the figure that the particles in the etched area on the surface of the electrode are relatively loose. This is because when the high-energy laser etches the active material layer, the binder is carbonized, and the active material and conductive agent in the active material layer become loose and form micron-sized dust.
[0218] 3. Use a contact angle meter to test the diffusion time of 1 mol / L LiPF6 electrolyte (solvent volume ratio EC:DMC:EMC=1:1:1) on the electrode, and use a high-speed camera to record the process pictures. Specifically, the electrodes provided in Example 8 and Comparative Example 1 were tested respectively, and three different positions were selected for each electrode for testing. The time from the beginning of the dripping of the electrolyte to the surface of the electrode to the time when the electrolyte on the surface of the electrode is completely absorbed by the electrode (the contact angle no longer changes) was recorded, and the average value of the time obtained by the three tests was calculated as the diffusion time of the electrolyte on the electrode, and the results are recorded in Table 3. It can be seen from the data in Table 3 that the diffusion time of the electrolyte on the active material layer is 28.583s, and the diffusion time on the conductive layer is 12.173s, indicating that the conductive layer can better infiltrate the electrolyte, and the conductive layer can accelerate the penetration rate of the electrolyte in the electrode and reduce the concentration polarization inside the electrode.
[0219] Table 3
[0220]
[0221] 4. Pole surface cleanliness test:
[0222] 4.1. For Example 8, at different stages of the electrode preparation, the cleanliness of the sample surface at different stages was investigated. The specific method was: Wear clean latex gloves to wipe the electrode surface, and observe the dirtiness of the position where the latex gloves contacted the electrode. The results are as follows: Fig.15 As shown. Among them, Fig.15 Figure (a) is a surface cleanliness test photo of the sample provided in step S2 (i.e., the sample before etching the active material layer). It can be seen from the photo that there is no obvious stain at the position of the latex glove contacting the active material layer, indicating that there is very little floating powder on the active material layer before etching; Fig.15Figure (b) is a surface cleanliness test photo of the sample provided in step S3 (i.e., the sample after the active material layer is etched). From the photo, it can be seen that there are obvious black stains at the position where the latex gloves contact the active material layer, indicating that after etching, the active material layer has serious floating powder; Fig.15 Figure (c) is a surface cleanliness test photograph of the sample provided in step S5 (i.e., the sample after the active material layer is covered with a conductive layer). From the photograph, it can be seen that there are no obvious stains at the position where the latex gloves contact the conductive layer, indicating that after the active material layer is covered with a conductive layer, the floating powder on the surface of the electrode is reduced.
[0223] 4.2. The pole pieces provided in Example 8 and Comparative Example 1 were respectively wound with the diaphragm and then separated, and the cleanliness of the diaphragm surface was observed. The results were as follows: Fig.16 As shown. Fig.16 It can be seen that the surface of the diaphragm wound around the electrode piece provided in Comparative Example 1 has obvious black dirt, while the surface of the diaphragm wound around the electrode piece provided in Example 8 is relatively clean, indicating that the active material layer has serious powder floating after laser etching, and after the active material layer after laser etching is covered with a conductive layer, the powder floating is significantly reduced.
[0224] 5. Rate performance test:
[0225] 5.1. Preparation of batteries: Batteries were prepared using the electrodes provided in Example 8 and Comparative Example 1 as negative electrodes (referred to as battery No. 1 and battery No. 2 for easy distinction), the positive electrode, separator and electrolyte of each battery were the same, wherein the active material layer of the positive electrode included lithium cobalt oxide (97.6wt%), PVDF (1.3wt%) and SP (1.1wt%), the separator was a polyethylene film, and the electrolyte was 1 mol / L LiPF6 electrolyte (solvent volume ratio EC:DMC:EMC=1:1:1).
[0226] 5.2. The prepared batteries were tested for rate performance according to the following test methods:
[0227] (1) Leave for 3 minutes;
[0228] (2) Constant current and constant voltage charging: charge at 0.2C to 4.47V, and cut off at 0.02C;
[0229] (3) Leave for 5 minutes;
[0230] (4) Constant current discharge: discharge to 2.75V at different test rates; the test rates are 0.2C, 0.5C, 1C, 1.5C, and 2C;
[0231] (5) Leave for 5 minutes;
[0232] (6) End, the test results show the battery capacity;
[0233] (7) The battery capacities obtained at different test rates were compared with the battery capacities at a test rate of 0.2C to obtain the capacity retention rates at different test rates. The results are recorded in Table 4.
[0234] Table 4
[0235] Group 0.2C discharge 0.5C discharge 1C discharge 1.5C discharge 2C discharge Example 8 100% 97.6% 95.5% 92.4% 74.5% Comparative Example 1 100% 97.7% 94.2% 82.9% 63.2%
[0236] It can be seen from the results in Table 4 that at low rates (0.2C, 0.5C), the capacity retention rates of battery No. 1 prepared using the electrode sheet provided in Example 8 and battery No. 2 prepared using the electrode sheet provided in Comparative Example 1 are close, and as the rate increases, the capacity retention rate of battery No. 1 is higher than that of battery No. 2, especially at high rates (1.5C, 2C), the capacity retention rate of battery No. 1 is significantly higher than that of battery No. 2, indicating that the provision of a conductive layer can significantly improve the rate performance of the battery.
[0237] 6. K value test:
[0238] 6.1. Preparation of batteries: Batteries were prepared using the pole pieces provided in Example 8 and Comparative Example 1 as negative electrodes, respectively. The positive electrode, separator and electrolyte of each battery were the same, wherein the active material layer of the positive electrode included lithium cobalt oxide (97.6wt%), PVDF (1.3wt%) and SP (1.1wt%), the separator was a polyethylene film, and the electrolyte was 1 mol / L LiPF6 electrolyte (solvent volume ratio EC:DMC:EMC=1:1:1).
[0239] 6.2. The prepared batteries were tested for K value according to the following test method: after the capacity was separated and the battery was left standing at room temperature for 96±4h, the OCV1 was tested to obtain the voltage U1, and then after the battery was left standing at room temperature for 48±4h (interval time t), the OCV2 was tested to obtain the voltage U2, and the K value was obtained by calculating (U1-U2) / t. The test results are recorded in Table 5.
[0240] Table 5
[0241] Group K Value Example 8 0.0422mV / h Comparative Example 1 0.0925mV / h
[0242] The K value of a battery refers to the voltage drop per unit time, usually expressed in mV / h, and is an indicator used to measure the self-discharge rate of a lithium battery.
[0243] It can be seen from the results in Table 5 that compared with Comparative Example 1, the K value of Example 8 is significantly reduced, which indicates that by adding a conductive layer to the electrode after laser etching, the conductive layer can cover the floating powder and reduce the risk of the floating powder entering the electrolyte and the diaphragm, thereby significantly reducing the K value of the battery.
[0244] The embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of the present application. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A pole piece, characterized in that: include: current collector; A composite layer is arranged on the current collector, and the composite layer includes a first active material layer and a liquid absorption layer which are arranged in sequence in a direction away from the current collector, the first active material layer has a first surface away from the current collector, and a recess extending from the first surface to the interior of the first active material layer is also formed on the first active material layer, and the liquid absorption layer covers the first surface and the inner surface of the recess.
2. The pole piece according to claim 1, characterized in that: The recess includes at least one of a groove and a through hole.
3. The pole piece according to claim 2, characterized in that: The concave portion is a long strip-shaped groove extending along a first direction of the first active material layer, and a length of the groove extending in the first direction is less than or equal to a length of the first active material layer in the first direction.
4. The pole piece according to claim 1, characterized in that: Along the direction approaching the current collector, the width of the recess remains unchanged or becomes smaller.
5. The pole piece according to claim 4, characterized in that: The sidewall of the concave portion is a straight wall or a curved wall, or, when cut along the thickness direction of the first active material layer, the cross section of the concave portion is V-shaped, trapezoidal, square, semicircular or elliptical.
6. The pole piece according to claim 1, characterized in that: There are multiple recesses, the recesses are spaced apart, and the distance between two adjacent recesses is 0.01 mm to 100 mm; and / or the depth of the recess is less than the thickness of the first active material layer; and / or the average width of the recess is 1 μm to 300 μm.
7. The pole piece according to claim 1, characterized in that: The thickness of the liquid absorbing layer is 0.2 μm to 50 μm; or, the thickness of the liquid absorbing layer is 0.2 μm to 10 μm; or, the porosity of the liquid absorbing layer is 5% to 99%.
8. The pole piece according to claim 1, characterized in that: The thickness of the first active material layer is greater than 30 μm; or the thickness of the pole piece is greater than 60 μm.
9. The pole piece according to claim 1, characterized in that: The liquid absorbing layer is a mixed layer including at least a first binder and a first conductive agent.
10. The pole piece according to claim 9, characterized in that: The first active material layer is a mixed layer including a first active material, a second binder, and a second conductive agent.
11. The pole piece according to claim 10, characterized in that: The mass content of the second conductive agent in the first active material layer is less than the mass content of the first conductive agent in the liquid absorbing layer; and / or the oil absorption value of the first conductive agent is greater than the oil absorption value of the first active material.
12. The pole piece according to claim 10, characterized in that: The content of the first active material in the first active material layer is greater than 50 wt %, and the content of the first conductive agent in the liquid absorbing layer is greater than 50 wt %.
13. The pole piece according to claim 10, characterized in that: In the first active material layer, the content of the second conductive agent increases along a direction approaching the current collector, and / or the first active material is first active material particles, and an average particle size of the first active material particles increases.
14. The pole piece according to claim 9, characterized in that: The first conductive agent includes at least one of a conductive carbon material and a conductive ceramic.
15. The pole piece according to claim 14, characterized in that: The conductive carbon material includes at least one of carbon black, carbon nanotubes, carbon fibers, acetylene black, graphite and graphene.
16. The pole piece according to claim 9, characterized in that: The specific surface area of the first conductive agent is 1 m 2 / g~1000m 2 / g; and / or, the D50 particle size of the first conductive agent is 1nm~50μm; and / or, the oil absorption value of the first conductive agent is greater than or equal to 500mL / 100g; and / or, the conductivity of the first conductive agent is 3000S·cm~12000S·cm.
17. The pole piece according to claim 9, characterized in that: The first binder includes at least one of carboxymethyl cellulose, polyacrylic acid, polyvinylidene fluoride, polytetrafluoroethylene and styrene-butadiene rubber.
18. The pole piece according to claim 9, characterized in that: The liquid absorbing layer includes 1 wt% to 80 wt% of the first conductive agent, 10 wt% to 99 wt% of the first binder, and the liquid absorbing layer further includes 0 wt% to 30 wt% of a dispersant.
19. The pole piece according to claim 18, characterized in that: The dispersant includes at least one of anhydride, polyvinyl pyrrolidone, sulfate, poly(N-vinyl acetamide), polyvinyl alcohol, sulfonate and polyethylene glycol; or, the dispersant includes at least one of ionic dispersants, non-ionic dispersants and polymer dispersants; and / or, the liquid-absorbing layer includes 58wt% to 75wt% of the first conductive agent, 12.5wt% to 30wt% of the first binder, and 8wt% to 12.5wt% of the dispersant.
20. The pole piece according to claim 1, characterized in that: The porosity of the liquid absorbing layer is at least greater than the porosity of the first active material layer.
21. The pole piece according to claim 1, characterized in that: The concave portion is a laser-etched portion.
22. The pole piece according to any one of claims 1 to 21, characterized in that: The composite layer further includes a second active material layer, which is disposed on the surface of the liquid absorbing layer and faces away from the first active material layer.
23. The pole piece according to any one of claims 1 to 21, characterized in that: The number of the composite layers on a single side of the current collector is multiple, and the multiple composite layers are stacked.
24. A method for preparing a pole piece, characterized in that: include: Preparing a first active material layer on a current collector, wherein the first active material layer has a first surface away from the current collector, and a concave portion extending from the first surface to an interior of the first active material layer is formed on the first active material layer; The first slurry is subjected to a film-forming treatment on the first surface and the recessed portions of the first active material layer to obtain a liquid absorbing layer.
25. The method for preparing a pole piece according to claim 24, characterized in that: The step of preparing a first active material layer on the current collector comprises: Performing a film-forming process on the current collector using the second slurry to obtain a first active material layer; Laser etching is performed on a portion of the first active material layer from a side of the first active material layer away from the current collector to generate a concave portion.
26. The method for preparing a pole piece according to claim 25, characterized in that: The step of performing a film-forming treatment on the first surface and the concave portion of the first active material layer with the first slurry to obtain a liquid absorbing layer comprises: Providing a first slurry, wherein the first slurry includes a first solvent, a first conductive agent, and a first binder; Applying the first slurry on the first surface and the inner surface of the concave portion to obtain a first wet film layer; The first wet film layer is dried to evaporate the first solvent, thereby obtaining a liquid absorbing layer.
27. The method for preparing a pole piece according to claim 26, characterized in that: The content of the first solvent in the first slurry is 10wt% to 97wt%; and / or, the solid content in the first slurry is 3wt% to 90wt%; and / or, the viscosity of the first slurry is 10cp to 15000cp; and / or, the first solvent includes at least one of water, N-methylpyrrolidone, ethylene glycol and isopropanol.
28. The method for preparing a pole piece according to claim 24, characterized in that: The preparation process of the first active material layer includes: Coating a second slurry on the current collector to obtain a second wet film layer, wherein the second slurry includes a first active material, a second binder, a second conductive agent, and a second solvent; The second wet film layer is dried to evaporate the second solvent, thereby obtaining a first active material layer.
29. The method for preparing a pole piece according to any one of claims 24 to 28, characterized in that: Also includes: Coating a third slurry on a side of the liquid absorbing layer away from the current collector to obtain a third wet film layer, wherein the third slurry includes a second active material, a third solvent, a third conductive agent and a third binder; The third wet film layer is dried to evaporate the third solvent, thereby obtaining a second active material layer.
30. A battery, characterized in that: A pole piece comprising the pole piece according to any one of claims 1 to 23 or a pole piece prepared by the method for preparing a pole piece according to any one of claims 24 to 29.
Citation Information
Cited By
Secondary battery and electric device
CN121709722A
Electrode sheet and preparation method therefor, and battery
EP4773210A1
Electrode sheet and preparation method therefor, and battery
WO2026076878A1